Determinants of Effective Implementation of Public Procurement Reservation Scheme in Kenya: A Case Study of the County Government of Nakuru (International Journal of Scientific Research and Management (IJSRM), 2022)
The study sought to examine the determinants of effective implementation of public procurement reservation scheme in Kenya. Specifically, the study analyzed the effect of Legal Compliance,Staff Competency and Organization Culture on the Implementation of Public Procurement Preference and Reservation scheme in the County Government of Nakuru. The target population comprised of 40 employees working as procurement professionals and accountants in the County Government of Nakuru, Kenya. The study adopted Census Sampling framework, Research hypotheses and descriptive research design. Both descriptive and inferential analysis was undertaken and the result be presented in frequency tables for ease of understanding and interpretations. The results of the study revealed that Legal compliance and organizational culture had a significant positive influence on effective implementation of public procurement preference and reservation scheme in Kenya. While supplier competency was found not to have significant influence on effective implementation of public procurement preference and reservation scheme in Kenya. The study recommends that that County Governments should comply with legal provision on preference and reservation as outlined in the public procurement and asset disposal Act 2015 and its regulations of 2020 and the constitution of Kenya 2010 by awarding 30% of tenders to the youth, people of disabilities, women and small and medium scale traders so as to promote social economic growth. The study also recommends that the organizations should have supplier forums to sensitize the disadvantage group on requirements and procedures of bidding. They should go an extra mile on educating them on how to use IFMIS procure to pay system when bidding with the county. It recommends that the Counties should cultivate a positive organization culture by paying attention to best practices such as; benchmarking and best practices sharing, change Management planning, adherence to ethical Employment Practices and conformance to the principle of Accountability in the conduct of their operations including but not limited to procurement processes. The research findings are expected to be beneficial to the county government management, procurement function and policy makers